Diphenyl diselenide dietary supplementation protects against methylmercury-chloride-induced immunotoxicity in the head kidney and spleen of grass carp (Ctenopharyngodon idella)via regulation of purinergic signaling and the NLRP3 inflammasome - Souza C.F. (2019)
© 2019 Elsevier Inc.This study aimed to evaluate whether dietary supplementation with diphenyl diselenide (Ph2Se2)would prevent the impaired immune and inflammatory responses elicited by methylmercury chloride (CH3HgCl)via protective effects on purinergic signaling in fish immune organs. Tissue and lymphocytic nucleoside triphosphate diphosphohydrolase (NTPDase)activity for adenosine triphosphate (ATP)and adenosine diphosphate (ADP)was downregulated in the head kidney and spleen of grass carp (Ctenopharyngodon idella)exposed to CH3HgCl. Concomitantly, adenosine deaminase (ADA)activity was upregulated. Further, nucleotide-binding oligomerization domain-like receptor (NLRP3)inflammasome gene expression was upregulated in the spleen and head kidney of CH3HgCl-exposed grass carp. Dietary supplementation with Ph2Se2 ameliorated these CH3HgCl-mediated alterations on purinergic enzymes, and their activities returned to baseline levels (except NTPDase activity for ADP). Based on these results, purinergic signaling in immune organs and lymphocytes can be considered a pathway linked to pro-inflammatory effects during exposure to environmental CH3HgCl concentrations, which may contribute to mortality of the affected fish. Since dietary supplementation with 3 mg Ph2Se2/kg in the feed prevented the CH3HgCl-induced alterations, it can be considered a potential suitable treatment to prevent impaired immune and inflammatory responses caused by Hg.